Declaring Tafseer for Humanity: Tafseer Methodology of Hassan Hanafi - Miftahuddin Miftahuddin (Institut Agama Islam Negeri (IAIN) Salatiga, 2020)
The purpose of this study is to construct the tafseer methodology of Hassan Hanafi in which he applies a new way of reading texts. The methodology used in this research is descriptive method using content analysis of literature. The main finding of this article is the existence of a new model of reading the text (Qur’an) offered by Hassan Hanafi in his Tafseer method. The uniqueness of the Tafseer methodology is the effort to incorporate social reality into the text. Departing from this reality, the text is